An Appraisal of the Concept of Beauty in Immanuel Kant’s Philosophy - Sasa, Michael Sunday (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
The central argument of this paper is to examine the idea of beauty in Kant’s thought. As it were, it is very difficult to have a universally acceptable standard or ground for Aesthetic judgement, it is mostly conceived that, an object of beauty must create attraction and appeal relatively to the human senses. This subjective conceptualization of Beauty has long been contested by philosophers like Plato, who held that Beauty is Objective. Like his contemporaries, Plato’s account has failed to resolve the problem of how to determine or adjudge an event, phenomenon, object or art work as beautiful. In this paper, Kant proposes a concept of beauty that goes beyond personal interest, pattern and structure of realities. He observed that if interest, structure and pattern make up beauty, then how would sublimity be achieved, which directs the pleasure principle in watching a pattern? Kant therefore defined beauty in terms of moments of quality, quantity, relation and modality. With these, Kant also conjectured that beauty is a symbol of morality. The conclusion that was reached in this paper is that, if Kant’s theory of beauty leads us to morality, then it is also therapeutic for moral crisis in Nigeria and the world at large.